Analisis kemampuan pemecahan masalah aljabar linier ditinjau dari self efficacy - Silviana Maya Purwasih; Erna Puji Astutik (IKIP Siliwangi, 2025)
Linear Algebra is often considered a difficult subject by students due to the complexity of its content and their limited problem-solving abilities. In addition to cognitive aspects, this ability is also influenced by affective factors, one of which is self efficacy. This study aims to investigate the problem-solving abilities of students in Linear Algebra, based on their self-efficacy levels. The research was conducted in the odd semester of the 2023/2024 academic year and involved participants from the 2022 cohort of the Mathematics Education Study Program who were enrolled in the Linear Algebra course. Data were collected through a self efficacy questionnaire, problem-solving tests, and interviews, and analyzed using the Miles and Huberman qualitative model. The findings indicate that students with high self efficacy demonstrated stronger abilities, especially in implementing solution plans and reviewing their answers. Meanwhile, students with moderate self efficacy tended to make calculation errors and were less likely to verify their results. These results suggest that self efficacy plays a significant role in comprehensive mathematical problem solving.